Autistic child with abdominal pain caused by foreign body ingestion - Özçelik, Zerrin; Gülcü, Didem (Journal of Surgery and Medicine, 2020)
Foreign body ingestion is an important condition with a potentially high mortality rate that is encountered in pediatric emergency departments and outpatient polyclinics. Foreign body ingestion occurs in 80% of children, especially those between 6 months and 3 years of age. However, in patients with mental disorders, in this case, autism, foreign body ingestion may occur at any age. A 16-year-old autistic patient presented with complaints of discomfort and restlessness, with no history of ingestion, however, we discovered through further investigations that the patient had in fact swallowed a foreign object. In this case, we would like to emphasize that autistic patients of any age can ingest foreign bodies, even without any suspicious history.